A brain microvasculature endothelial cell‐specific viral vector with the potential to treat neurovascular and neurological diseases. Issue 6 (22nd April 2016) - Körbelin, Jakob; Dogbevia, Godwin; Michelfelder, Stefan; Ridder, Dirk A; Hunger, Agnes; Wenzel, Jan; Seismann, Henning; Lampe, Melanie; Bannach, Jacqueline; Pasparakis, Manolis; Kleinschmidt, Jürgen A; Schwaninger, Markus; et al.
Abstract: Gene therapy critically relies on vectors that combine high transduction efficiency with a high degree of target specificity and that can be administered through a safe intravenous route. The lack of suitable vectors, especially for gene therapy of brain disorders, represents a major obstacle. Therefore, we applied an in vivo screening system of random ligand libraries displayed on adeno‐associated viral capsids to select brain‐targeted vectors for the treatment of neurovascular diseases. We identified a capsid variant showing an unprecedented degree of specificity and long‐lasting transduction efficiency for brain microvasculature endothelial cells as the primary target of selection. A therapeutic vector based on this selected viral capsid was used to markedly attenuate the severe cerebrovascular pathology of mice with incontinentia pigmenti after a single intravenous injection. Furthermore, the versatility of this selection system will make it possible to select ligands for additional in vivo targets without requiring previous identification of potential target‐specific receptors. Synopsis: A capsid AAV2 mutant, AAV‐BR1, with tropism for the neurovascular endothelium, generated by selecting an AAV2 display peptide library in vivo, holds promise as a gene therapy vector for neurovascular and potentially other central nervous system diseases. Capsid mutants with a specific redirected tropism can be selected from AAV display peptide libraries in vivo . One mutant, AAV‐BR1, effectively transduces neurovascular (blood–brain barrier‐associated) endothelial cells in vivo and in vitro . AAV‐BR1 can be used to ameliorate the severe neurological impairments in a mouse model of incontinentia pigmenti. Abstract : A capsid AAV2 mutant, AAV‐BR1, with tropism for the neurovascular endothelium, generated by selecting an AAV2 display peptide library in vivo, holds promise as a gene therapy vector for neurovascular and potentially other central nervous system diseases.